Implementation of disaster risk reduction management activities in flood-prone communities of a highly urbanized city in Central Visayas - Gaudiel, Arvin (Technium Social Sciences Journal, 2023)
Background. The study aimed to determine the extent of implementation of the disaster risk reduction management activities on flooding in the areas of prevention and mitigation, preparedness, response, and rehabilitation and recovery in the flood-prone communities in a highly urbanized city in the Philippines as assessed by DRRM implementers and community leaders. Likewise, it identified the challenges in implementing the disaster risk reduction management activities on flooding encountered by the implementers. The study sought if there is a significant difference in the extent of implementation of disaster risk reduction management in the area of prevention and mitigation, preparedness, response and recovery when respondents are grouped according to income classification, population size, and land area. Method. In this study it use a descriptive-comparative research approach. The respondents were the DRRM implementers and community leaders of flood-prone communities in a highly urbanized city in Central Visayas. They were determined using incidental sampling. Before conducting the study,the request letter stipulating the nature and the details of the research of the Implementation of Disaster Risk Reduction Management Activities on flood prone areas in Central Visayas was obtained. After which the researcher prepares the questionnaire to be distributed to the proper respondents. Before answering the actual research instrument, the identified respondents were advised about the study, specifically its purpose, scope, nature and the parts of the questionnaire. They were ask to answer the questionnaire and the data collection proper commenced after the agreement. After the data collection, they submit the questionnaire and treated with confidentiality with respect to the respondent of the study. The information gathered was analyzed with the help of the statistician. Descriptive and comparative analysis were utilize using the appropriate statistical tools in analyzing and interpreting the data on the implementation of disaster risk reduction management activities in flood-prone communities of a highly urbanized city in Central Visayas. Results. Overall the extent of implementation of DRRM activities in flood-prone communities as a whole is great extent. In terms of the thematic areas, recovery is in moderate extent, while the other areas are great extent. There is no significant difference in the extent of implementation of DRRM activities in flood-prone communities when respondents are grouped according to income, population and land area in all the thematic areas except for preparedness. Improper disposal of solid waste by the local people is the most common challenge observed in prevention and mitigation by the respondents. Delayed implementation of city/barangay projects for disaster risk reduction is the most common challenge observed in preparedness by the respondents. In response, delayed responsive action is the most common challenge observed by the respondents. Lastly, in recovery, the lack of local attention to those affected people is the most common challenge observed by the respondents. Overall, Improper disposal of solid waste by the local people is the most common challenge observed on the DDRM activities on flooding. Conclusion The great extent of the implementation of disaster risk reduction management activities in flooding revealed a need for continuous improvement in terms of disaster preparedness, prevention and mitigation, response, and recovery. Moreover, when respondents were grouped according to income, population, and land area, these variables showed no significant difference. This implies that regardless of their categories, the implementation of both classes showed no significant difference, except for the thematic area of preparedness. This means that the implementers are resilient and objective driven in their assignments on DRRM activities on flooding. There is also room for improvement where the implementation of DRRM activities on flooding can be improved up to a very great extent. In the area of preparedness, the implementers and community leaders must focused on the difference on the variables for the reason that regardless of income, population or land area, the implementers and community leaders must focus and implement all the thematic areas of the DRRM activities on flooding especially in the area of preparedness. The implication on the result reflects the actual implementation by our implementers and community leaders and can be basis for future studies. Limitation of Findings. The study's findings are limited since the study was conducted in a highly urbanized city in the Visayas. They do not reflect the opinion of the office where the respondents are employed or served. They do not also reflect the opinion of the City of Bacolod and the barangays involved in this study. This study also identified the challenges in implementing disaster risk reduction management activities on flooding. Other limitation on the findings is other persons did not give their approval to be subjected to the study. There is also limitation to the sampling and instrument since only incidental sampling is used and not stratified random sampling. The interpretation of the results in the study in not approximate in the result on the actual implementation of the activities. There are also limited studies relating to the extent of implementation on DRRM activities in flood prone areas. Lastly, the study is limited to only 102 respondents which only a small number compared to the implementers and community leaders in the whole city. Practical Application. The researcher proposed a Strategic Plan to strengthen the implementation of the DRRM activities on flooding in their local communities. Furthermore, observing these proposed programs, projects, and activities would create a positive outlook for the community and reach a very great extent of implementation to ensure that they follow all the measures all the time for their safety. Direction for Future Research They may explore other variables that affect the implementation of disaster risk reduction management activities in flooding. Moreover, another study may be conducted exploring the DRRM measures and fund utilization of the community leaders in addressing disaster-related concerns. Furthermore, the future researchers can enhance their research by lifting the limitations mentioned in this study. An example is to involve many respondents and barangays or choose a more sound sampling instrument to the study.